Entrepreneurial university icon: Stanford and Silicon Valley as innovation and natural ecosystem. Issue 4 (August 2022) - Etzkowitz, Henry
The author explicates the cultural DNA and take-off trajectory of an exemplary entrepreneurial university and its emerging focus on sustainability. Entrepreneurial initiatives, emanating from the engineering school in the late 19th century, spread to the physical sciences in the 1930s and to the biological sciences and medicine by the 1970s. A concerted and compressed academic development strategy sought researchers with related interests across disciplines, assuming that teaching could be diversified from these critical cores. A multi-pronged financial strategy included attracting federal research funds, leasing university land, technology transfer income and endowment from gifts and equity in university-originated firms in varying past and future proportions. Bottom-up initiatives proliferated, filling technology transfer and start-up support gaps in the entrepreneurial ecosystem. Recently, some innovation initiatives have been shuttered as the Administration has tacked towards addressing climate change though a microscopic initiative. Given an institutionalized and legitimated culture and infrastructure of entrepreneurship and innovation, these dual institutional logics operate in tandem symbiosis, mutually fructifying each other.